Black beauty - - Sewell, Anna; Freeman, Michael Lacey (Pakistan : Maqbool Books, 2017)
This adaptation of Black Beauty presents the classic tale through the eyes of a gentle horse. Told in simple, clear language suitable for beginner-level English learners (A1), it explores themes of kindness, friendship, and the experiences of the protagonist throughout his life. Accompanied by vocabulary glossaries, comprehension activities, grammar support, and an exit test, it helps students build reading confidence, language understanding, and context$1 (Bideal for young or ESL readers.s
Keywords: English Literature - Text Book